Research needs for cementitious building materials with focus on Europe - Karen Scrivener; Mohsen Ben Haha; Patrick Juilland; Christophe Levy (RILEM Technical Letters, 2023)
The needs for research on cementitious materials are reviewed with a focus on Europe. These are considered under 8 topics: clinker production, alternatives to Portland cement, composite cements based on Portland clinker, concrete, admixtures, durability, recycling, digitisation in concrete construction, and, carbon capture and use or storage; finally, the key research questions and their potential for CO2 reduction are summarised in a “Watermelon” diagram with a list of 30 key questions to be addressed (see Appendix).